Securing Energy for Development in West Bank and Gaza : Summary Report - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2017)
The Palestinian Territories face significant energy security challenges, already severe in Gaza, but also emerging in the West Bank.The Palestinian Territories rely primarily on Israeli imports to meet its electricity needs.The only large scale generation capacity in the Palestinian Territories is the troubled Gaza Power Plant.The Palestinian electricity sector has undergone a number of institutional reforms, which still require further consolidation.Measures to improve energy efficiency can also make a valuable contribution to energy security going forward. Palestine’s existing National Energy Efficiency Action Plan aims to make savings equivalent to one percentage point of energy consumption annually through to 2020, focusing primarily on reducing electricity consumption by improving the energy efficiency of residential buildings. A much more ambitious action plan is under consideration by the Palestinian Energy and National Resources Authority for 2020-2030, and aims to save 5 percent of the energy consumption anticipated during that period. The new strategy encompasses high impact energy efficient appliances (such as heaters, fridges and air conditioners), further tightening of efficiency standards for buildings, and smart grid infrastructure to allow consumers to participate in the energy market as demand response. Investments to improve energy efficiency are proven to be much more cost-effective than expanding power generation capacity.